Fundamental analysis in predicting stock returns for Indonesia transportation and logistics companies during Covid-19 pandemic - Agustin, Isnaini Nuzula; Lukito, Ivander (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The development of companies in the transportation and logistics sector has been hindered by the increasing Covid-19 pandemic, which minimizes outdoor activities. This study aims to determine the fundamental factors affecting companies’ stock returns during the Covid-19 pandemic. Data collection was obtained from annual financial reports available on the official website of idx.co.id during the period 2017-2021, resulting in 81 samples, and panel data regression analysis was used as the research method. The results of the study showed that return on assets had a positive and significant effect on stock returns, while net profit margin had a negative and significant effect on stock returns. Additionally, other variables did not have a significant effect on stock returns. The limitation of this research was that it only used one sector of companies and only tested 21 companies that met the criteria. Perkembangan perusahaan sektor transportasi dan logistik semakin terhambat seiring meningkatnya pandemi Covid-19 yang meminimalisir kegiatan di luar rumah. target dalam penelitian ini mengetahui faktor fundamental perusahaan terhadap pengembalian saham pada masa pandemi Covid-19. Pengumpulan data didapatkan dari laporan keuangan tahunan yang tersedia di website resmi idx.co.id selama periode 2017-2021 sehingga didapatkan 81 sampel dan menggunakan analisis regresi data panel sebagai metode penelitian. Hasil penelitian menunjukkan bahwa return on asset berpengaruh positif dan signifikan terhadap pengembalian saham dan net profit margin berpengaruh negatif dan signifikan terhadap pengembalian saham. Selain itu, variabel lainnya tidak berpengaruh signifikan terhadap pengembalian saham. Limitasi penelitian ini adalah keterbatasan jumlah data mengingat periode Covid-19 baru dimulai sejak 2020 dan masih berjalan hingga saat ini.